TEACHING ENGLISH SPEAKING SKILLS THROUGH TASK-BASED LANGUAGE TEACHING - Amelia Yulia Rahmah, - (2023)
This study aimed to investigate how task-based language teaching (TbLT) contributed to students' speaking skills and the students' perception towards TbLT implementation. This research employed a case study design involving nine students in one public junior high school in Bandung, West Java. The data were collected using three instruments such as observation, students' audio and interviews. All of the data were analyzed by adapting thematic analysis from Creswell (2009). The findings of this study revealed two themes related to the aim of this study: TbLT's contribution to students' speaking skills and students' perceptions towards TbLT implementation. The results of the study showed that TbLT improved students' speaking skills in five aspects, namely (1) content and structure of description, (2) the speech sound, (3) spoken grammar, (4) vocabulary use and (5) slips and errors. Furthermore, the students perceived TbLT as having clear objectives, reminding them of real-world communications, motivating them to learn English, engaging their attention, allowing them to communicate, having doable tasks and having interconnected activities. Research for future studies is recommended to include more task types, involve more participants, seek the challenges faced by teachers and students during TbLT implementation and assess interaction aspects of speaking nature.